The non-coordinating anion 1, 1, 3, 3-tetracyano-2-propoxy-propenide as an anion-π donor in cis-diaquabis(2, 2′-dipyridylamine)zinc and its cadmium analog: Luminescence properties, Hirshfeld analysis and central-atom induced polymorphism. (27th July 2017) - Lehchili, Fouzia; Setifi, Fatima; Liu, Xue; Saneei, Anahid; Kučeráková, Monika; Setifi, Zouaoui; Dušek, Michal; Poupon, Morgane; Pourayoubi, Mehrdad; Reedijk, Jan
Graphical abstract: The synthesis, structure and properties of cis-[M(H2 O)2 (2, 2′-dpa)2 ][tcnopr]2, are reported for M = Zn and Cd. These compounds have been fully characterized by elemental analysis, FT-IR spectroscopy, powder XRD and X-ray single-crystal diffraction. The metal ions are cis-octahedrally coordinated and exhibit 3D supramolecular architectures, including multiple anion-π interactions. Abstract: The synthesis, structure and properties of cis-diaquabis(2, 2′-dipyridylamine)zinc bis(1, 1, 3, 3-tetracyano-2-propoxy-propenide), [Zn(H2 O)2 (2, 2′-dpa)2 ][tcnopr]2, I, and its isomorphous Cd analog, II, are reported. These two coordination compounds were prepared through hydrothermal reactions of Zn(II)/Cd(II) acetate with potassium 1, 1, 3, 3-tetracyano-2-propoxy-propenide (tcnopr – = [(NC)2 CC(OPr)C(CN)2 ] − ) in the presence of 2, 2′-dipyridylamine (dpa = C10 H9 N3 ) as a co-ligand. Both new compounds were fully characterized by elemental analysis, FT-IR spectroscopy, powder XRD and X-ray single-crystal diffraction. Single-crystal X-ray analysis has revealed that compoundsI andII are isostructural containing octahedrally coordinated metal ions, and exhibit 3D supramolecular architectures, including multiple anion-π interactions. Furthermore, the photoluminescence properties in the solid state at room temperature and Hirshfeld surfaces analysis to understand the packing have also been investigated in detail.